2003
DOI: 10.1002/mrc.1300
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis. Part 40: a theoretical and NMR investigation of the conformations of cis‐ and trans‐cyclopentane‐1,3‐diol

Abstract: The conformations of cis-(1) and trans-cyclopentane-1,3-diol (2) have been studied by ab initio (Gaussian 98) and molecular mechanics (PCMODEL) calculations and by NMR spectroscopy. The calculations gave two low-energy conformations for (1), 1A and 1B, both with axial hydroxyl groups. Two conformations with equatorial hydroxyl groups (1C and 1D) were found but with much higher energy (ca 4.0 kcal mol −1 ). These novel findings are considered with previous data on cyclopentanol and cis-and trans-cyclopentane-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…A general trend of overestimating the J-couplings relative to the experimental values is observed in Table VII, similar to the results in Ref 23 . The ring J-couplings, 3 J H 1, H 2 and 3 J H 2, H 3 , show the largest deviation from experimental observation, the Karplus parameters of which are derived for cyclopentane-1,3-diol 87 . Other than the error introduced by the simplified molecular model of the Karplus equation parameterization, Mobli et al suggested that further sources of error include exclusion and/or simplification of solvent effects, basis set limitations and intrinsic properties of DFT 23,88 during the parameterization of Karplus relationships.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…A general trend of overestimating the J-couplings relative to the experimental values is observed in Table VII, similar to the results in Ref 23 . The ring J-couplings, 3 J H 1, H 2 and 3 J H 2, H 3 , show the largest deviation from experimental observation, the Karplus parameters of which are derived for cyclopentane-1,3-diol 87 . Other than the error introduced by the simplified molecular model of the Karplus equation parameterization, Mobli et al suggested that further sources of error include exclusion and/or simplification of solvent effects, basis set limitations and intrinsic properties of DFT 23,88 during the parameterization of Karplus relationships.…”
Section: Resultsmentioning
confidence: 78%
“… a Simulation coupling constants calculated according to Karplus equations in ref 23 b Parameters for Karplus equation obtained from ref 87 c Karplus equations derived for the N-acetyl fragment based on ref 86 …”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…This equation is a function of the electronegativity of the substituents, the H-C-C-H torsion angle and the orientation of each substituent relative to the coupled protons. In a recent investigation, 47 it was noted that the 1 H, 1 H coupling constants calculated with this equation for the C 4 .C 5 fragment in cis-and trans-cyclopentane-1,2-diol were much larger than the observed values. An alternative equation was derived for the C.CH 2 .CH 2 .C fragment in five-and six-membered rings using a simple form of the Karplus equation 48 with accurate experimental couplings of molecules in known conformations to give Eqn (7), and this equation is implemented in the CHARGE routine.…”
Section: H H Coupling Constantsmentioning
confidence: 73%
“…It optimizes the 3D structures of the compounds with a molecular mechanics force field and calculates vicinal 3 J(H,H) couplings by a modified Karplus equation (including parameters for cyclopentanes). [16] We applied the algorithm BEST for coupling constant calculations (See Sup. Info.).…”
Section: Qc Calculation Of 3 J(hh) Coupling Constants and Evaluationmentioning
confidence: 99%